Experiential Function Analysis Of Recep Tayyip Erdogan’s Speech In The 74th Session Of The United Nations General Assembly In New York - Ade Safia Rahma (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
: This study deals with the experiential function analysis of Recep Tayyip Erdogan’s Speech in the 74th session of the United Nations General Assembly in New York. This study aimed to find out the types of experiential function found in the Recep Tayyip Erdogan’s speech, to identify function that often occurs on Recep Tayyip Erdogan’s speech, and to elaborate the reason for occurrence of dominant type in Recep Tayyip Erdogan's speech in the 74th session of the United Nations general assembly in New York. Descriptive qualitative research was applied in this study. The data of research were taken from Recep Tayyip Erdogan’s Speech, 99 clauses found in this speech. From the data analysis, it was found that the relational process was 70 clauses (70.71%), followed by mental process with the percentage was 25 clauses (25.25%), and the existential process with the percentage was 4 clauses (4.04%). The realization of process types of experiential function occurred because the speech has the grammatical and systematically reasons. The speaker used process types of experiential function for indicating something that has many references depends on speaker’s means which can explain words or sentences to be understood by the audiences. The most dominant type of experiential function used in the Recep Tayyip Erdogan’s speech in the 74th session of the United Nations General Assembly in New York was relational process that the information given is about having and being which the speaker expresses his idea to persuade the audience through his speech.Keywords: Analysis, Experiential Function, Recep Tayyip Erdogan’s Speech